Use of agro-industrial waste from the processing of oilseeds and Amazonian fruits - HERMINO, Vanessa Leal de Queiroz; SILVA, Edson Pablo; ABREU, Ellen Rocha de; MOTA, Daniel Nascimento; NEVES, Siglia Maria; TORRES, Vanderson Gabriel Souza; FREITAS, Flávio Augusto de; PEREIRA JÚNIOR, Nei (Food Science and Technology, 2025)
The processing of fruits and vegetables in general generates a significant amount of waste, which is often discarded in the environment, losing the potential for using it in obtaining and/or developing other value-added products. Within this theme, some waste arising from the processing of Amazonian fruits and oilseeds, such as açaí and andiroba, deserves attention due to the large volume of waste generated from these species. The development of new ways of using these as raw materials to obtain products with high added value becomes a challenge, which can directly impact the preservation of the environment by reducing the disposal of these wastes and socioeconomic conditions, since viable alternatives of use can generate demand for specialized work. This literature review presents a survey of recent data on two raw materials: açaí and andiroba, in addition to the current picture on production, market, composition, and applications.